Pengaruh Ekstrak Daun Kersen (Muntingia calabura L.) sebagai Disinfektan Alami terhadap Daya Hambat dan Penurunan Total Bakteri di Ruang Penampungan Susu - Bunga Nada Azzahra; Eulis Tanti Marlina; Ellin Harlia (Jurnal Teknologi Hasil Peternakan, 2022)
Cherry leaves are an alternative material that can be used as a natural disinfectant because they contain active compounds in the form of flavonoids, saponins, and tannins which can work as antibacterial compounds in milk storage rooms. The purpose of this study was to determine the effect of using cherry leaves extract as a natural disinfectant through testing the inhibition zone and calculating the total number of bacteria in the milk storage room, and for knowing the concentration of cherry leaves which showed the best inhibition in the milk storage room. The study was conducted experimentally using Completely Randomized Design (CRD) and continued with Tukey's Test and Orthogonal Polynomial Test with three treatments, namely P1 (30% concentration), P2 (40% concentration), and P3 (50% concentration) with five replications. The results showed that cherry leaves extract was able to inhibit gram-positive bacteria in the form of cocci and bacilli and gram-negative bacteria in the form of cocci.. Extract of cherry leaves with a concentration of 50% was the most effective concentration as a natural disinfectant with an average inhibition zone formed of 9.73 mm against gram-positive bacteria cocci form, 9.22 mm against gram-positive bacteria in the form of bacilli, and 9.40 mm against bacteria gram negative cocci form, and the average decrease in the total number of bacteria was 92.51% on the floor.